Synthesis, characterization, and electrochemical and electrochromic properties of sandwich dilutetium tetraphthalocyanine - ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2004)
A new sandwich-tpype dilutetium tetraphthalocyanine 4 has been synthesized by the reaction of dimeric lutetium(m) phthalocyanine 3 with two equiv. of dilithium octakishexylthiophthalocyanine in amyl alcohol. Compound 3 was prepared from 4',5',4,5-tetraiminoisoindoline(1,4,7,10-tetrathia-12-crown-4) 1,4,5-bis(hexylthio)-1,2-diiminoisoindoline 2 and lutetium acetate in amyl alcohol. Compounds 3 and 4 were characterized by elemental analysis, UV/visible, IR, H-1 NMR and ESR spectroscopy. The electrochemical and electrochromic properties of 3 and 4 have been examined by cyclic voltammetry. Both 3 and 4 displayed well-defined electrochromic behavior.
Keywords: LANGMUIR-BLODGETT-FILMS; LIQUID-CRYSTALLINE BEHAVIOR; SPECTROSCOPIC CHARACTERIZATION; PHTHALOCYANINE COMPLEXES; REDOX PROPERTIES; LUTETIUM DIPHTHALOCYANINE; ELECTRICAL-CONDUCTIVITY; ADSORPTION PROPERTIES; YTTRIUM(III); ELECTRODES